Factors Affecting Quality of Life in Pediatric Patients with Type I Diabetes Mellitus - Muhammad Azeem Sarwar Gill, Ramsha Zaheer, Samia Ijaz, Aamir Iqbal, Ayesha Ali, Abiha Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Globally, the incidence rate of type 1 diabetes has increased , with the most significant rise in annual incidence among children under the age of five. Depression in these patients disproportionately affects vulnerable populations with type 1 diabetes and interventions targeting this population are therefore relevant. Objective: The objective of this study to determine the quality of life in pediatric patients with type I diabetes mellitus. Methodology: The study was Cross-sectional study was conducted after IRB approval in Unit II, Department of Pediatrics, Mayo Hospital, Lahore for the duration of six months from December 2022 to May 2023. The quality of life scale was graded into different category high quality of life score is more than 80 falls in and moderate 60 to 80 and below than 60 falls in low quality of life Results: Total 95 patients were in the study cases, 61 (64.2 %) were male patients while 34 (35.8 %) were female patients. The mean age of our study cases was 9.96 ± 1.64 years. Of these 95 study cases, 41 (43.2 %) belonged to rural areas and 54 (56.8 %) belonged to urban areas. Poor socioeconomic status was noted in 63 (66.3%), while 32 (33.7%) were middle income and 57 (60.0%) mothers were illiterate. The mean body mass index of our study cases was 24.21 ± 1.36 kg/m2 and obesity was present in 06 (6.3 %) of our study cases Conclusion: The mean disease duration was 2.89 ± 1.13 years and 54 (56.8 %) had more than 2.5 years of illness. Quality of life was intermediate in 36 (37.9%) and 59 (62.1%) had poor quality of life. Very high frequency of poor quality of life was noted in our study among diabetic children. Quality of life was significantly associated with gender, age, residential status, socioeconomic status, maternal literacy, and prolonged disease duration. Clinicians treating such patients must screen their patients for the quality of life for time management. This will decrease the burden of related morbidities and improve the quality of life for these patients. Keywords: Type 1 diabetes mellites , quality of life, children,